MAQASHID SHARIAH AS THE FOUNDATION OF ISLAMIC ECONOMIC DEVELOPMENT: A CONCEPTUAL LITERATURE REVIEW - Salma Anisa Pertiwi (PT. Samudra Solusi Profesional, 2025)
Maqashid Shariah, commonly defined as the objectives of Islamic law, constitutes the ethical and philosophical foundation of Islamic economics. Unlike conventional economic paradigms that primarily emphasize growth and efficiency, Islamic economic development grounded in Maqashid Shariah prioritizes holistic human welfare (maslahah), social justice, and ethical sustainability. This conceptual study aims to systematically review and synthesize scholarly literature on the role of Maqashid Shariah in shaping Islamic economic development frameworks. Drawing upon classical Islamic jurisprudence and contemporary economic thought, this paper examines how the five essential objectives of Shariah protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal) serve as normative benchmarks for economic policies, institutional design, and development outcomes (Al-Shatibi, 2003; Chapra, 2008; Auda, 2008). Through a qualitative systematic literature review, this study analyzes peer-reviewed journals, policy reports, and authoritative academic sources discussing the conceptual integration of Maqashid Shariah into Islamic economic systems. The findings indicate that Maqashid-based economic development promotes inclusive growth, ethical financial practices, poverty alleviation, and human development, particularly in Muslim-majority countries. Empirical discussions from the literature further demonstrate that Maqashid-oriented indicators align closely with multidimensional development measures such as the Human Development Index, especially in the Indonesian context (Chapra, 2016; Harahap & Fauzi, 2020). However, the literature also highlights challenges related to operationalization, regulatory alignment, and measurement frameworks. This study concludes that Maqashid Shariah offers a comprehensive conceptual foundation for Islamic economic development, bridging normative Islamic values with contemporary development discourse and providing strategic insights for policymakers and scholars.